(untitled) (Damascus University Journal for the economic and Political sciences, 2021)
The research deals with the subject of "Occidentalism" and its concept which means the study of the West (its languages, literature, sciences, arts, economics, history, philosophies, customs, cultures and civilizations ...) by the Oriental thinkers. The study also deals with the reality of "Occidentalism" in contemporary thought, indicating the motives of its establishment and its desired goals, and its importance in creating a balanced dialogue among civilizations, not to mention its role in advancing the development of the countries and peoples of the East at all levels. The research presents an analytical study of one of the famous thoughted in the Islamic Republic of Iran, Muhammad Mujtahid Shabstari, and his philosophy, views and visions in this field after the Islamic Revolution. The study examines these aspects, but in contrast, it overlooks the most important difficulties and problems that the field of “Occidentalism” still suffers from. The aim of this research is to present some solutions through which the “Occidentalism” can make its way for the better and become a science with integrated methodology and tools to help achieve its objectives.